Sporting Chance: Indigenous Participation in Australian Sport History - Gorman, Sean (University of Technology Sydney, 2010)
For many non-Indigenous Australians the only time they have any engagement with Indigenous peoples, history or issues is through watching sport on television or being at a football match at ground like the MCG. This general myopia and indifference by settler Australians with Indigenous Australians manifests itself in many ways, but perhaps most obscenely in the simple fact that Indigenous Australians die nearly 20 years younger than the rest of Australia’s citizens. Many non-Indigenous Australians do not know this. Sport in many ways has offered Indigenous Australians a platform from which to begin the slow, hard process for social justice and equity to be actualised. This paper will discuss the participation of Indigenous Australians in sport and show how it has enabled Indigenous Australians to create a space so that they can speak out against the injustices they have experienced and to improve race relations going into the future. The central contention is that through sport all Australians can begin a process of engaging with Indigenous history as a means to improve race relations between the two groups.